Planktonic Foraminiferal Biostratigraphy of the Kometan Formation from Kurdistan Region, NE Iraq - Mohammed Sulaiman; Majid Al-Mutwali; Ali Al-Juboury; Fadhil Lawa (Iraqi Geological Journal, 2023)
The Kometan Formation is widely spread in northeastern Iraq and is mostly composed of deep marine carbonates, with a predominance of planktonic foraminiferal assemblages throughout its sequences. Two outcrop sections, Smaquli and Tabin, were chosen to study the biostratigraphy of the Kometan Formation. The study identified 32 planktonic foraminiferal species belonging to 12 genera. According to stratigraphic distribution and the relative distribution of planktonic foraminifera assemblages, the study demonstrated the possibility of subdividing the sequence of the Kometan Formation into five foraminiferal biozones, including: Marginotruncana schneegansi Partial Range Zone, Dicarinella primitiva Interval Zone, Dicarinella concavata Interval Zone, Dicarinella asymetrica Total Range Zone, Globotruncanita elevata Partial Range Zone. The Planktonic zones were correlated with other zonal schemes inside and outside Iraq. They are considered to be extending from Late Turonian to Early Campanian.